Influence of the P-delta Effect and Stiffness Irregularity on the Structural Behavior of Reinforced Concrete Buildings - Zavala, D. J. (2022)
In this research, the influence of the stiffness irregularity and the p-delta effect on the structural behavior of a reinforced concrete building is analyzed. The main objective is to determine the impact of the stiffness irregularity and the p-delta effect on the structural behavior in regular and irregular buildings. First, the linear dynamic analysis procedure is performed in order to determine the structural response in terms of drifts, shear force and moments per floor. Subsequently, we proceed with the nonlinear static analysis procedure to obtain the capacity curve of the structure. The post elastic stiffness and the overall ductility of the structure are determined from the capacity curve. Finally, a comparative analysis of the responses from the linear and nonlinear analysis is carried out to determine the percentage variation of the results. When analyzing the structures that consider the stiffness irregularity and the p-delta effect, variations of up to 16.50%, 11.00% and 14.00% have been obtained in drifts, shear force and moments per floor respectively, which are considerable values. When the p-delta effect is considered in structures with the presence of stiffness irregularity, there is a variation in stiffness of up to 59.85%. With this result it is explained that the p-delta effect produces a greater degradation of the overall stiffness of the structure.